The Influence of IT Affordance and Customer Engagement on Actual Purchase in Tiktok Live Commerce in Indonesia - Nugroho, Yonatan Chondro; Sugiarto, Catur (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze the influence of information technology affordability (IT affordance) on consumer behavior in live commerce on the TikTok application, with a focus on the role of customer engagement as an intervening variable. Using quantitative methods with a descriptive and survey approach, data was collected through questionnaires distributed online to 420 respondents who were users of the live shopping feature on TikTok. The analysis results show that various IT affordance factors, including visibility, meta voicing, guided shopping, trading, triggered attending, and social connecting, have a significant effect on consumer engagement (flow, trust, and interactivity). Furthermore, consumer involvement has been proven to influence purchase intention, which ultimately has an impact on actual purchases. The implications of this research provide insight for developers and business actors in designing more effective online sales strategies, taking into account the importance of interaction and trust in improving consumer experience and encouraging purchases on live commerce platforms. This research also provides a reference for further research to explore other factors that influence consumer behavior in the context of e-commerce.